2013
DOI: 10.3892/etm.2013.1048
|View full text |Cite
|
Sign up to set email alerts
|

Arrival time parametric imaging using Sonazoid-enhanced ultrasonography is useful for the detection of spoke-wheel patterns of focal nodular hyperplasia smaller than 3 cm

Abstract: It is considered difficult to make a definitive diagnosis of focal nodular hyperplasia (FNH) of <3 cm when using conventional diagnostic imaging modalities. Typical FNH imaging findings are: i) central scar formation, ii) nutrient vessels extending radially from the center and iii) the presence of Kupffer cells. In a clinical setting, identification of a spoke-wheel pattern formed by nutrient vessels extending radially is a key feature in the diagnosis of FNH. In this study, we investigated the detection rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The arrival time was defined as zero and represented the time differences in different colors. A few studies demonstrated that CPI was useful in the diagnosis of hepatic parenchymal diseases [11,12] and in identifying spoke-wheel patterns of FNH [13] . To our knowledge, this is the first study to analyze whether CPI could provide useful information to differentially diagnose atypical hemangioma and liver metastases.…”
Section: Introductionmentioning
confidence: 99%
“…The arrival time was defined as zero and represented the time differences in different colors. A few studies demonstrated that CPI was useful in the diagnosis of hepatic parenchymal diseases [11,12] and in identifying spoke-wheel patterns of FNH [13] . To our knowledge, this is the first study to analyze whether CPI could provide useful information to differentially diagnose atypical hemangioma and liver metastases.…”
Section: Introductionmentioning
confidence: 99%
“…(E) The increase in the echogenicity in the Tx group was more prominent at POD 56 than at POD 14. was used to detect liver tumors in animal models (24,25) and in the clinic (26). Currently, the second-generation contrast agent, Sonazoid 1 (NC100100), is widely used to detect many types of gastroenterological tumor (27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…It enables color display reflecting real-time changes in hemodynamics. In hepatic lesions, it has been reported that parametric images may be used to obtain detailed hemodynamic information of the hepatic parenchyma and make a diagnosis of hepatic disease [8][9][10][11]. In breast lesions, previous studies suggest that parametric imaging is useful for differentiating between malignant and benign breast tumors [12,13].…”
Section: Introductionmentioning
confidence: 99%